Odontogenic cysts in children and adolescents: a 21-year retrospective study - Vinicius Gomes Serra; Daniele Meira Conde; Rogério Vera Cruz Ferro Marques; Cláudio Vanucci Silva de Freitas; Fernanda Ferreira Lopes; Maria Carmen Fontoura Nogueira da Cruz (Universidade Estadual de Campinas, 2015)
Aim: To investigate the distribution of odontogenic cysts in patients aged 0 to 18, referred to Department of Pathology, University Hospital of the Federal University of Maranhão, Brazil, to determine the most common types of lesions and their distribution according to gender and anatomical site involved. Methods: Histopathological data were collected from a database of lesions classified as odontogenic cysts that were indicated for surgical removal and histopathological analysis. Data were subjected to descriptive analysis. Results: Thirty cases of odontogenic cysts were identified, and dentigerous cysts were the most frequent (n=17). Most occurrences were in males (66.7%) and the most frequent site was the posterior mandible (73.3%). Conclusions: Odontogenic cysts in children and adolescents are mostly developmental cysts, especially dentigerous cysts, occurring predominantly in males, with a predilection for the posterior mandible.